Kinin B1 receptor regulates interactions between neutrophils and endothelial cells by modulating the levels of Mac-1, LFA-1 and intercellular adhesion molecule-1. Issue 3 (April 2015) - Figueroa, Carlos D; Matus, Carola E; Pavicic, Francisca; Sarmiento, Jose; Hidalgo, Maria A; Burgos, Rafael A; Gonzalez, Carlos B; Bhoola, Kanti D; Ehrenfeld, Pamela
Kinins are pro-inflammatory peptides that mimic the cardinal features of inflammation. We examined the concept that expression levels of endothelial intercellular adhesion molecule-1 (ICAM-1) and neutrophil integrins Mac-1 and LFA-1 are modulated by the kinin B1 receptor (B1 R) agonist, Lys-des[Arg 9 ]bradykinin (LDBK). Stimulation of endothelial cells with LDBK increased the levels of ICAM-1 mRNA transcripts/protein, and also of E-selectin and platelet endothelial adhesion molecule-1. ICAM-1 levels increased in a magnitude comparable with that produced by TNF-α. This stimulatory effect was reduced when endothelial cells, which had been previously transfected with a B1 R small interfering RNA, were stimulated with LDBK, under comparable conditions. Similarly, LDBK produced a significant increase in protein levels of LFA-1 and Mac-1 integrins in human neutrophils, an effect that was reversed by pretreatment of cells with 10 µg/ml cycloheximide or a B1 R antagonist. Functional experiments performed with post-confluent monolayers of endothelial cells stimulated with LDBK and neutrophils primed with TNF-α, and vice versa, resulted in enhanced adhesiveness between both cells. Neutralizing Abs to ICAM-1 and Mac-1 reduced the adhesion between them. Our results indicate that kinin B1 R is a novel modulator that promotes adhesion of leukocytes to endothelial cells, critically enhancing the movement of neutrophils from the circulation to sites of inflammation.